2021
DOI: 10.1111/aogs.14259
|View full text |Cite
|
Sign up to set email alerts
|

Maternal polycystic ovary syndrome and attention deficit hyperactivity disorder in offspring at 3 years of age: Odense Child Cohort

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution-NonCo mmercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Two Swedish registry-based studies reported a stronger association between maternal PCOS exposure and ADHD in female offspring than in male offspring ( 10 , 13 ), whereas the Finnish population study reported a similar risk estimate for boys and girls ( 14 ). In contrast, the Odense child cohort study involving 1776 mothers reported a positive association (adjusted OR = 2.20, 95% CI: 1.20–4.02) between maternal PCOS and ADHD in male offspring but not in female offspring (adjusted OR = 0.43, 95% CI: 0.13–1.42) ( 15 ). Our findings are consistent with those from the Odense cohort study, showing a tendency for a stronger association between maternal PCOS and offspring ADHD in boys than in girls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two Swedish registry-based studies reported a stronger association between maternal PCOS exposure and ADHD in female offspring than in male offspring ( 10 , 13 ), whereas the Finnish population study reported a similar risk estimate for boys and girls ( 14 ). In contrast, the Odense child cohort study involving 1776 mothers reported a positive association (adjusted OR = 2.20, 95% CI: 1.20–4.02) between maternal PCOS and ADHD in male offspring but not in female offspring (adjusted OR = 0.43, 95% CI: 0.13–1.42) ( 15 ). Our findings are consistent with those from the Odense cohort study, showing a tendency for a stronger association between maternal PCOS and offspring ADHD in boys than in girls.…”
Section: Discussionmentioning
confidence: 99%
“…For example, two Swedish studies reported a stronger association between maternal PCOS and offspring ADHD in girls than in boys ( 10 , 13 ). In contrast, the Odense Child Cohort in Denmark reported a significant correlation between maternal PCOS and ADHD symptoms in boys but not in girls ( 15 ). Therefore, further studies are required to clarify sex differences in the association between maternal PCOS and offspring ADHD.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…There is emerging evidence linking PCOS and psychiatric disorders in PCOS patients and their offspring. Women with PCOS have greater odds of depression, anxiety disorder, 7–23 bipolar affective disorder, schizophrenia, social phobia, obsessive‐compulsive disorder, eating disorders, sleep disturbance, and attention deficit hyperactivity disorder (ADHD), 4,24–35 as well as an increased prevalence of ADHD, autism spectrum disorder (ASD), chronic tic disorder, and other behavior disorders in their children 26,36–43 . Furthermore, women with PCOS have a higher risk of both persistence of existing psychiatric disorders and the emergence of new psychiatric disorders during follow up 17,44,45 .…”
Section: Introductionmentioning
confidence: 99%
“…greater odds of depression, anxiety disorder, [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] bipolar affective disorder, schizophrenia, social phobia, obsessive-compulsive disorder, eating disorders, sleep disturbance, and attention deficit hyperactivity disorder (ADHD), 4,[24][25][26][27][28][29][30][31][32][33][34][35] as well as an increased prevalence of ADHD, autism spectrum disorder (ASD), chronic tic disorder, and other behavior disorders in their children. 26,[36][37][38][39][40][41][42][43] Furthermore, women with PCOS have a higher risk of both persistence of existing psychiatric disorders and the emergence of new psychiatric disorders during follow up. 17,44,45 Concurrently, psychological disorders may make PCOS treatment more challenging.…”
mentioning
confidence: 99%